2012
DOI: 10.1021/am302041b
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Induced Tooth Remineralization

Abstract: Inspired by mussel bioadhesion in nature, dopamine is extensively used for biomaterial surface modification. In this study, we coated dopamine on demineralized enamel and dentin surfaces to evaluate the effect of polydopamine coating on dental remineralization. Dental slices containing enamel and dentin were first etched with 37% phosphoric acid for 2 min, followed by immersion in a 2 mg/mL freshly prepared solution of dopamine (10 mM Tris buffer, pH 8.5) for approximately 24 h at room temperature in the dark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
145
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(161 citation statements)
references
References 23 publications
8
145
0
1
Order By: Relevance
“…145 In a study by Zhou et al, dental slices containing both enamel and dentin were coated with polydopamine and immersed in a supersaturated solution of calcium and phosphate for several days. 151 Characterization of surface properties using scanning electron microscope (SEM) and Xray powder diffraction (XRD) revealed that the polydopamine coating greatly enhanced dentin mineralization despite no observed differences in enamel mineralization. These results suggest that polydopamine can bind to the collagen matrix and thus provide a new nucleation site for mineral deposition of dentin.…”
Section: Applications In Tissue Engineeringmentioning
confidence: 99%
“…145 In a study by Zhou et al, dental slices containing both enamel and dentin were coated with polydopamine and immersed in a supersaturated solution of calcium and phosphate for several days. 151 Characterization of surface properties using scanning electron microscope (SEM) and Xray powder diffraction (XRD) revealed that the polydopamine coating greatly enhanced dentin mineralization despite no observed differences in enamel mineralization. These results suggest that polydopamine can bind to the collagen matrix and thus provide a new nucleation site for mineral deposition of dentin.…”
Section: Applications In Tissue Engineeringmentioning
confidence: 99%
“…[35] In recent years, various biomaterials have been employed for remineralizing demineralized dentin such as fluoride, bioactive glasses, amorphous calcium phosphate (ACP)-releasing resins, and dopamine. [36][37][38][39][40] However, all of the above are only suitable for remineralizing partially demineralized dentin, which relies on the epitaxial deposition of calcium and phosphate ions over remnant crystallites. [41] In some clinical situations, such as the hybrid layers that are created by etch-and-rinse adhesive systems and in the superficial portion of caries-affected dentin lesions that are left behind after minimally invasive caries removal, dentin is completely demineralized.…”
Section: Collagen Mineralizationmentioning
confidence: 99%
“…Polydopamine possesses covalent and non-covalent bonding capabilities for a broad range of organic, inorganic and metallic substrates [2], harboring potential applications in the challenging field of antibacterial [3], antifungal [4], antifouling [5], [6], drug delivery vehicle [7], biosensor [8], cell culture [9], tissue engineering [10][12] and so on. However, to author's knowledge, dopamine solution is usually polymerized for at least several hours prior to surface modification/deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are three major dopamine polymerization processes: static, shake, and stir. With regard to the static method, substrates are submerged in dopamine solution for 16 h [10], 18 h [3], overnight [21], [22] or 24 h [12] at room temperature. In shake method, dopamine solutions are shaken to achieve uniform PDA film on the substrate at quite different reaction temperature and time (such as 1 h at ambient temperature [23], 24 h at ambient temperature [24] and 8 h at 30°C [25]).…”
Section: Introductionmentioning
confidence: 99%